Preliminary design of an automated white board cleaner (2014)
The work presented in this paper is on the preliminary design and fabrication of an automated whiteboard cleaner. The objective here in is to reduce the man-power involved in cleaning white boards after use. Though the use of smart boards is increasing, many institutions in the developed and developing world still make use of white boards. The Autodesk software was used for the CAD drawing and thereafter the design analyses and fabrication were done. The auto-board was designed to be powered by a single phase 0.6 HP electric motor. The chain drive parameters were determined based on estimations of the centre distance between the sprockets, the required cleaning time, number of sweeps, total number of chain links and the expected performance. The cleaning efficiency of the auto-white board cleaner is estimated to be better than the manual operation when the equipment is fully completed.